The effect of amorphous coating on high temperature oxidation resistance of Ni-based single crystal superalloy. (1st April 2023) - Wang, Mingming; Cheng, Xiaopeng; Jiang, Wenxiang; Cao, Tianci; Liu, Xianqiang; Lu, Junxia; Zhang, Yuefei; Zhang, Ze
Abstract: Amorphous Al2 O3 coating was prepared on Ni-based single crystal superalloy via atomic layer deposition (ALD) for high temperature oxidation protection. The oxygen inward transport and outward-cation diffusion were hindered by amorphous Al2 O3 coating, and the coated alloy showed high oxidation resistance. The low oxygen partial pressure at the alloy/coating interface altered the alloy oxidation behavior, allowing the priority oxidation of protective Al and Cr elements. The oxidation process was controlled by the growth of Cr2 O3 and Al2 O3 . The coating exhibited high spallation resistance. Degradation of the coating, the formation of NiAl2 O4 phase in amorphous Al2 O3 layer, was observed. Highlights: Amorphous Al2 O3 coating was proposed and prepared on Ni-based single crystal superalloy. The amorphous Al2 O3 coating improved oxidation resistance and exhibited high adhesion. The amorphous Al2 O3 coating altered the oxidation behavior of the alloy. The effect mechanism of amorphous Al2 O3 coating on the alloy oxidation was discussed.